Developing a benchmark model for renovated, nearly zero-energy, terraced dwellings. (15th January 2022) - Attia, Shady; Canonge, Théophile; Popineau, Mathieu; Cuchet, Mathilde
Graphical abstract: Highlights: Development of a benchmark model for renovated nearly zero energy terraced buildings. The average energy use intensity per household was 29 kWh/m 2 /year. Models validated with four-year monitoring data on energy consumption. Middle old families dominate households, and their occupancy profiles are presented. Findings on energy needs and use intensity are useful in temperate and continental climates. Abstract: Brussels is one of the European cities with the most significant number of Passive House buildings on the continent. In the Brussels-Capital Region, the nearly zero-energy building obligations implemented is implemented since 2010. The Brussels-Capital Region has set up ambitious energy standards for new constructions. These standards target 'nearly zero' or 'very low energy consumption and are inspired by the 'passive house standard, ' where high-energy performance is first achieved. Ten years after boasting this groundbreaking policy, many renovated, terraced houses are renovated to comply with the nearly zero-energy building requirements. Therefore, this study aims to develop an energy performance data set and one building performance simulation benchmark model for nearly zero-energy dwellings in Brussels. The study reports an inventory and field survey conducted on a terraced house renovated after the year 2010. An analysis of energy consumption (electricity and natural gas) and a walkthrough survey were conducted. A building performance simulation model is created in EnergyPlus to benchmark the average energy consumption and building characteristics. The estimate's validity has been further checked against the public statistics and verified through model calibration and utility bill comparison. The benchmark has an average energy use intensity of 29 kWh/m 2 /year and represents terraced single-family houses after renovation. The paper provides a timely opportunity to evaluate the actual performance of nearly zero-energy terraced houses. The findings on energy needs and use intensity are useful in temperate and continental climates.